Advances in nanostructured composites. Volume 1, Carbon nanotube and graphene composites - Aliofkhazraei, Mahmood (Boca Raton : CRC Press, 2018)
Composites and nanocomposites are used in cases where longdurability and strength of components are required; i.e., where highstress levels, erosion processes and multiphase environments are present, including the parts under collision and impact, the parts under rotating motion and erosion (like excavation drills in oil and gas wells). The first volume of this book aims to provide a guide for fabrication of new nanocomposites mainly based on carbon nanotubes and graphene. The main topics of this volume are: Application of Nano-powders for Formation of Metal Matrix of Composites, Conjugated Polymer Nanocomposites, Biopolymer Nanocomposites, Dental Nanocomposites, Graphene-based Nanocomposites for Electrochemical Energy Storage, Polymer/Filler Composites for Optical Diffuse Reflectors, Synthesis and Applications of LDH-Based Nanocomposites, Rubber--CNT Nanocomposites, Nanocomposite Fibers with Carbon Nanotubes, Fabrications of Graphene Based Nanocomposites for Electrochemical Sensing of Drug Molecules, Recent Advances in Graphene Metal Oxide Based Nanocomposites.
Contents INTRODUCTION TO NANOCOMPOSITES FABRICATION Application of Nano-Powders for Formation of Metal Matrix of Composites Vladimir A. Popov Nanocomposites: Recent Trends, Developments and Applications Ravindra Pratap Singh Conjugated Polymer Nanocomposites Pradip Kar Biopolymer Nanocomposites -- From Basic Concepts to Nanotechnologies Magdalena Aflori Dental Nanocomposites Eric Habib, Ruili Wang and Julian Zhu Graphene-Based Nanocomposites for Electrochemical Energy Storage Chunwen Sun Non-Conventional Techniques for Characterization of Nano Hybrid Materials Based on Clays Denis T. Araújo, Breno F. Ferreira, Tiago H. da Silva, Maisa A. Moreira, Katia J. Ciuffi, Eduardo J. Nassar, Vicente Rives, Miguel A. Vicente, Raquel Trujillano, Antonio Gil, Sophia Korili and Emerson H. de Faria Nanostructured Composite Materials for CO2 Activation Anurag Kumar, Pawan Kumar and Suman L. Jain Polymer/Filler Composites for Optical Diffuse Reflectors Yue Shao and Frank Shi Synthesis and Applications of LDH-Based Nanocomposites Alireza Khataee and Samira Arefi-Oskoui Magnetic Anisotropy of Nanocomposites Made of Magnetic Nanoparticles Dispersed in Solid Matrices Costica Caizer Biopolymer Layered Silicate Nanocomposites: Effect on Cloisite 10 A on Thermal, Mechanical and Optical Properties Okan Akin, Hale Oguzlu, Onur Ozcalik and Funda Tihminlioglu CNT AND GRAPHENE NANOCOMPOSITES Rubber -- CNT Nanocomposites M. Balasubramanian and P. Jawahar Nanocomposite Fibers with Carbon Nanotubes, Silver, and Polyaniline Nuray Ucar and Nuray Kizildag Processing and Mechanical Properties of Carbon Nanotube Reinforced Metal Matrix Composites Abdollah Hajalilou, Ebrahim Abouzari-lotf, Katayoon Kalantari, Hossein Lavvafi and Amalina Binti Muhammad Afifi Fabrications of Graphene Nanocomposites for Electrochemical Sensing of Drug Molecules Tien Song Hiep Pham, Peter J. Mohan and Aimin Yu Toward CNTs; Functionalization and Their Sensing Applications Nada F. Atta, Hagar K. Hassan and Ahmed Galal CNT-Based Bio-Nanocomposite as Electrochemical Sensors S.K. Suja and G. Jayanthi Kalaivani Polypropylene Nanocomposites Containing Multi-Walled Carbon Nanotubes and Graphene Oxide by Ziegler-Natta Catalysis Jin-Yong Dong and Yawei Qin Recent Advances in Graphene Metal Oxide based Nanocomposite for Energy Harvesting/ Thermoelectric Application Abhijit Dey Synthesis and Properties of Carbon Nanotube/Alumina Nanocomposites Soumya Sarkar and Probal Kumar Das
OCLC-licensed vendor bibliographic record.
Keywords: Nanocomposites (Materials); Carbon nanotubes; SCIENCE / Life Sciences / General; TECHNOLOGY / Material Science